The cohort size-wage relationship in Europe - John Moffat; Duncan Roth (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
The demographic and education composition of European countries is changing: the population share of young individuals is declining while that of the highly educated is rising. This paper estimates the impact of cohort size on wages using data on 21 European countries covering 2007-2010 to cast light on the economic consequences of changes in the profile of the labour force. The effect of cohort size on wages is identified through an instrumental variables strategy which, in contrast to previous analyses of European data, addresses selfselection into geographical areas as well as into educational groups. The results support the hypothesis that cohort size has a negative effect on male wages, particularly for the highly educated. However, these negative cohort size effects are not persistent.
Keywords: J10; J21; J31; 330; Cohort size; wages; causal effect; instrumental variables; EU-SILC